2018
DOI: 10.1108/er-04-2017-0093
|View full text |Cite
|
Sign up to set email alerts
|

Labour reputation and financial performance: is there a causal relationship?

Abstract: Purpose The purpose of this paper is to analyse if there is a circular relationship of causality between the labour dimension of corporate social performance (CSP) and corporate financial performance (CFP). Design/methodology/approach The sample is formed by the best companies to work for in Spain according to the labour reputation (LR) ranking developed by MERCO from 2006 to 2013. This study overcomes the limitations of previous studies using the panel data methodology (System generalised method of moments)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 83 publications
0
13
0
1
Order By: Relevance
“…The research on the relationship between CSR and CFP is saturated (e.g., References [13,14]). Many studies found that CSR can improve CFP through a variety of channels, such as labor reputation [15], customer awareness [16], labor productivity [17], and improved transparency [18]. Some studies found a negative relationship (e.g., Reference [19]), citing an agency problem or shareholder-stakeholder conflicts.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…The research on the relationship between CSR and CFP is saturated (e.g., References [13,14]). Many studies found that CSR can improve CFP through a variety of channels, such as labor reputation [15], customer awareness [16], labor productivity [17], and improved transparency [18]. Some studies found a negative relationship (e.g., Reference [19]), citing an agency problem or shareholder-stakeholder conflicts.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Looking at other performance metrics, McGuire et al [3] found significant correlations between social responsibility and return on assets (ROA), Debt/Assets, Beta and standard deviation of total returns. More recent studies focus on different aspects of CSR and their impacts on firm outcomes, including labor reputation [18], customer awareness [19], labor productivity [20] and improved transparency [21]. In this study, we attempt to use numerous firm and executive characteristics to determine if consistent results can be obtained.…”
Section: Firm Performance and Corporate Social Responsibilitymentioning
confidence: 97%
“…with the perspective of CSR) of these constructs is also seldom conveyed in earlier studies (e.g. Augusto de Oliveira et al., 2019 ; Dee, 2020 ; Hertig et al., 2020 ; Odriozola et al., 2017 ; Salam and Farooq, 2020 ; Sinthupundaja et al., 2018 ; Tracy et al., 2020 ) on the subject matter. As a result, the renunciation of primary objectives of the implementation of CPP, SQ and CSR has inevitably convulsed and led to a major fratricidal subjugation of the underlying philosophy of individual/customer care (i.e.…”
Section: Introductionmentioning
confidence: 91%
“…A number of studies on workplace performance (e.g. Chung, 2016 ; Corvalan, 2018 ; Karanges et al., 2015 ; Odriozola et al., 2017 ; Sutherland, 2017 ) have confirmed that engaged employees are more creative and more productive for their organizations. According to Rameshkumar (2019) EE has a strong impact on organizational commitment.…”
Section: Literature Reviewmentioning
confidence: 99%